A high-strength concrete additive and preparation method thereof

By using fly ash, montmorillonite and modified wear-resistant fillers (silicon nitride and zirconia) in concrete additives, the problem of insufficient wear resistance of concrete in the prior art is solved, and high strength and high wear resistance are achieved Performance improvement.

CN116135809BActive Publication Date: 2024-12-24SHENZHEN CHANGDAO ENG CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310293692.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2024-12-24
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

While the existing concrete additives have not fully improved their wear resistance while increasing the strength of concrete.

Method used

Use high-strength concrete additives composed of fly ash, montmorillonite, wear-resistant filler (composed of silicon nitride and zirconium oxide) and water reducing agent, and improve the wear-resistant performance of concrete by preparing modified wear-resistant filler .

Benefits of technology

The wear resistance and compressive strength of concrete are significantly improved, and the overall performance of concrete is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004142390050000081
    Figure BDA0004142390050000081
Patent Text Reader

Abstract

The present invention relates to the technical field of concrete additive preparation, and specifically discloses a high-strength concrete additive and a preparation method thereof. The high-strength concrete additive is characterized in that it contains the following components in parts by weight: 30 to 50 parts of fly ash; 10 to 20 parts of montmorillonite; 10 to 20 parts of anti-wear filler; 1 to 5 parts of water reducer; the anti-wear filler consists of silicon nitride and zirconium oxide. The high-strength concrete additive can not only improve the strength of concrete, so that the prepared concrete has higher strength; at the same time, the high-strength concrete additive can also effectively improve the wear resistance of concrete by adding anti-wear fillers composed of silicon nitride and zirconium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete additive preparation, and in particular to a high-strength concrete additive and a preparation method thereof. Background Art

[0002] Concrete additives refer to substances added during the concrete mixing process to improve concrete properties. For example, Chinese invention patent 201810458205.2 discloses a high-strength permeable concrete additive and its preparation method. The additive comprises: 0.5-3 parts micropowder, 1-4 parts ammonium sulfate, 1-4 parts potassium sulfate, 1-4 parts sodium sulfate, 1-4 parts magnesium chloride, 6-12 parts ferrous sulfate, 1-4 parts ferrous sulfate, 9-14 parts calcium chloride, 0.05-0.3 parts sodium gluconate, and 55-70 parts water. This concrete additive is primarily composed of inorganic substances, has low toxicity, and exhibits excellent aging resistance. Containing a large amount of metal ions and the addition of micropowder, it effectively enhances the strength and permeability of permeable concrete.

[0003] Chinese invention patent 201810156469.2 discloses an environmentally friendly concrete additive comprising the following components by weight: 12-15 parts organically modified montmorillonite, 1-4 parts organic boron fiber, 1-3 parts polyether phosphate amine salt, and 1-4 parts surfactant. Compared to concrete containing conventional concrete additives, concrete containing this environmentally friendly concrete additive is less expensive, less polluting, and exhibits significantly improved performance, with enhanced strength, flowability, durability, and impermeability.

[0004] The inventors have found in actual applications that although existing concrete additives can improve the strength of concrete to a certain extent, their wear resistance of concrete needs to be further improved. Summary of the Invention

[0005] In order to overcome at least one of the technical problems existing in the prior art, the present invention first provides a high-strength concrete additive.

[0006] The technical solutions of the present invention are as follows:

[0007] The present invention first provides a high-strength concrete additive, which comprises the following components in parts by weight:

[0008] 30-50 parts fly ash; 10-20 parts montmorillonite; 10-20 parts anti-wear filler; 1-5 parts water reducer;

[0009] The anti-wear filler consists of silicon nitride and zirconium oxide.

[0010] The present invention provides a high-strength concrete additive with a completely new composition. The high-strength concrete additive can not only improve the strength of concrete, so that the prepared concrete has higher strength; at the same time, the high-strength concrete additive can also effectively improve the wear resistance of concrete by adding anti-wear fillers composed of silicon nitride and zirconium oxide.

[0011] Preferably, the high-strength concrete additive comprises the following components in parts by weight:

[0012] 40-50 parts of fly ash; 15-20 parts of montmorillonite; 15-20 parts of anti-wear filler; 1-3 parts of water reducer.

[0013] Most preferably, the high-strength concrete additive comprises the following components in parts by weight:

[0014] 45 parts of fly ash; 15 parts of montmorillonite; 15 parts of anti-wear filler; 2 parts of water reducing agent.

[0015] Preferably, the weight ratio of silicon nitride to zirconium oxide in the anti-wear filler is 4 to 6:1.

[0016] Most preferably, the weight ratio of silicon nitride to zirconium oxide in the anti-wear filler is 5:1.

[0017] Preferably, the water reducing agent is selected from sodium lignin sulfonate.

[0018] Preferably, the anti-wear filler is a modified anti-wear filler;

[0019] The modified anti-wear filler is prepared by the following method:

[0020] (1) adding melamine to methanol and stirring to dissolve to obtain a melamine methanol solution;

[0021] (2) silicon nitride and zirconium oxide are added to a melamine methanol solution and mixed evenly, and then the methanol is evaporated to obtain a mixture;

[0022] (3) calcining the mixture at 400-600° C. in an inert gas atmosphere for 2-4 hours to obtain a calcined product;

[0023] (4) mixing the calcined product with a solution containing a modifier to obtain a modified mixture;

[0024] (5) The modified mixture is dried to obtain the modified anti-wear filler.

[0025] The inventors found in their research that the modified anti-wear filler obtained by modifying the anti-wear filler composed of silicon nitride and zirconium oxide by the above method can significantly improve the wear resistance of concrete compared to the anti-wear filler composed of silicon nitride and zirconium oxide.

[0026] At the same time, the modified anti-wear filler obtained by modifying the anti-wear filler composed of silicon nitride and zirconium oxide by the above method can also effectively improve the compressive strength of concrete compared with the anti-wear filler composed of silicon nitride and zirconium oxide.

[0027] Preferably, the modifier is selected from N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride or tetradecyldimethylbenzylammonium chloride.

[0028] More preferably, the modifier is selected from a combination of N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride.

[0029] More preferably, the weight ratio of N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride to tetradecyldimethylbenzylammonium chloride is 2-3:1-3.

[0030] Most preferably, the weight ratio of N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride to tetradecyldimethylbenzylammonium chloride is 3:2.

[0031] The inventors further discovered in their research that the choice of modifier has an important influence on the anti-wear performance of concrete by the prepared modified anti-wear filler; the degree of improvement in the anti-wear performance of concrete by the modified anti-wear fillers prepared by using different modifiers is different.

[0032] The inventors surprisingly discovered during their research that when a modified anti-wear filler is prepared using a mixed modifier consisting of N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride as a modifier, the degree of improvement in the wear resistance of concrete is significantly higher than that of a modified anti-wear filler prepared using only N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride or tetradecyldimethylbenzylammonium chloride as a modifier.

[0033] Preferably, the mass fraction of melamine in the melamine methanol solution is 5-10%.

[0034] Most preferably, the mass fraction of melamine in the melamine methanol solution is 8%.

[0035] Preferably, in step (2), the ratio of the total weight of silicon nitride and zirconium oxide to the amount of melamine methanol solution is 1 kg: 2 to 3 L.

[0036] The weight ratio of silicon nitride to zirconium oxide is 4 to 6:1.

[0037] Most preferably, the weight ratio of silicon nitride to zirconium oxide in the anti-wear filler is 5:1.

[0038] Preferably, the ratio of the calcined product to the solution containing the modifier is 1 kg: 2 to 3 L.

[0039] Preferably, the mass fraction of the modifier in the solution containing the modifier is 4 to 6%;

[0040] Most preferably, the mass fraction of the modifier in the solution containing the modifier is 5%.

[0041] Preferably, the high-strength concrete additive further contains 1 to 5 parts of a dispersant.

[0042] Most preferably, the high-strength concrete additive further comprises 3 parts of a dispersant.

[0043] Preferably, the dispersant is selected from any one or a combination of more than one of sodium hexametaphosphate, lauryl acylammonium methylsulfate and N-octadecyl octadecanoic acid amide.

[0044] Most preferably, the dispersant is selected from sodium hexametaphosphate, lauryl acylammonium trimethylsulfate and N-octadecyl octadecanoic acid amide.

[0045] The weight ratio of sodium hexametaphosphate, lauryl acylammonium trimethyl sulfate and N-octadecyl octadecanoic acid amide is 1-2:1-2:1-2;

[0046] Most preferably, the weight ratio of sodium hexametaphosphate, lauryl acylammonium methylsulfate and N-octadecyl octadecanoic acid amide is 1:1:1.

[0047] Theoretically, the addition of a dispersant helps disperse fly ash, montmorillonite, and anti-wear fillers in concrete, thereby further enhancing their effectiveness in concrete and further improving the strength and wear resistance of the high-strength concrete additive of the present invention. However, the inventors discovered through research that conventional dispersants or combinations of dispersants do not adequately disperse fly ash, montmorillonite, and anti-wear fillers in concrete. Consequently, conventional dispersants or combinations of dispersants do not significantly enhance the strength and wear resistance of concrete using the high-strength concrete additive of the present invention, which contains fly ash, montmorillonite, and anti-wear fillers.

[0048] The inventors surprisingly discovered during their research that when a mixed dispersant consisting of sodium hexametaphosphate, lauryl acylammonium trimethyl sulfate, and N-octadecyl octadecanoic acid amide is used as a dispersant, the high-strength concrete additive comprising fly ash, montmorillonite, and an anti-wear filler of the present invention can further significantly improve the strength and wear resistance of concrete. However, the use of one or a combination of any two of sodium hexametaphosphate, lauryl acylammonium trimethyl sulfate, and N-octadecyl octadecanoic acid amide, or the use of other dispersants or combinations of dispersants, does not enable the high-strength concrete additive of the present invention to further significantly improve the strength and wear resistance of concrete.

[0049] The present invention also provides a method for preparing the above-mentioned high-strength concrete additive, which comprises the following steps:

[0050] The high-strength concrete additive is obtained by uniformly mixing fly ash, montmorillonite, anti-wear filler or modified anti-wear filler and water reducer.

[0051] Beneficial effects: The present invention provides a high-strength concrete additive with a completely new composition. The high-strength concrete additive can not only improve the strength of concrete, so that the prepared concrete has higher strength; at the same time, the high-strength concrete additive can also effectively improve the wear resistance of concrete by adding anti-wear fillers composed of silicon nitride and zirconium oxide. DETAILED DESCRIPTION

[0052] The present invention is further explained below with reference to specific examples, but the examples do not limit the present invention in any form.

[0053] Example 1 Preparation of high-strength concrete additive

[0054] Raw materials by weight: 45 parts of fly ash; 15 parts of montmorillonite; 15 parts of anti-wear filler; 2 parts of sodium lignin sulfonate as a water reducer;

[0055] The anti-wear filler is composed of silicon nitride and zirconium oxide in a weight ratio of 5:1;

[0056] Preparation method: fly ash, montmorillonite, anti-wear filler and water reducer are uniformly mixed to obtain the high-strength concrete additive.

[0057] Example 2 Preparation of high-strength concrete additive

[0058] Raw materials by weight: 45 parts of fly ash; 15 parts of montmorillonite; 15 parts of modified anti-wear filler; 2 parts of water reducing agent sodium lignin sulfonate;

[0059] The modified anti-wear filler is prepared by the following method:

[0060] (1) Add an appropriate amount of melamine to methanol, stir and dissolve to obtain a melamine methanol solution with a mass fraction of 8%;

[0061] (2) Weighing silicon nitride and zirconium oxide in a weight ratio of 5:1, then adding melamine methanol solution and mixing evenly, and then evaporating the methanol to obtain a mixture;

[0062] (3) calcining the mixture at 500°C for 3 h in an argon atmosphere to obtain a calcined product;

[0063] (4) mixing the calcined product with a solution containing 5% by mass of a modifier to obtain a modified mixture;

[0064] (5) drying the modified mixture to obtain the modified anti-wear filler;

[0065] In step (2), the ratio of the total weight of silicon nitride and zirconium oxide to the melamine methanol solution is 1 kg:2 L;

[0066] In step (4), the ratio of the calcined product to the solution containing the modifier is 1 kg:2 L; the modifier is selected from N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride.

[0067] Preparation method: fly ash, montmorillonite, modified anti-wear filler and water reducer are uniformly mixed to obtain the high-strength concrete additive.

[0068] Example 3 Preparation of high-strength concrete additive

[0069] The composition by weight of the raw materials and the preparation method are the same as those in Example 2.

[0070] The difference between Example 3 and Example 2 is that different modifiers are used in the preparation process of the modified anti-wear filler; the modifier in Example 2 is tetradecyl dimethyl benzyl ammonium chloride.

[0071] The modified anti-wear filler is prepared by the following method:

[0072] (1) Add an appropriate amount of melamine to methanol, stir and dissolve to obtain a melamine methanol solution with a mass fraction of 8%;

[0073] (2) Weighing silicon nitride and zirconium oxide in a weight ratio of 5:1, then adding melamine methanol solution and mixing evenly, and then evaporating the methanol to obtain a mixture;

[0074] (3) calcining the mixture at 500°C for 3 h in an argon atmosphere to obtain a calcined product;

[0075] (4) mixing the calcined product with a solution containing 5% by mass of a modifier to obtain a modified mixture;

[0076] (5) drying the modified mixture to obtain the modified anti-wear filler;

[0077] In step (2), the ratio of the total weight of silicon nitride and zirconium oxide to the melamine methanol solution is 1 kg:2 L;

[0078] In step (4), the ratio of the calcined product to the solution containing the modifier is 1 kg:2 L; the modifier is selected from tetradecyldimethylbenzylammonium chloride.

[0079] Example 4 Preparation of high-strength concrete additive

[0080] The composition by weight of the raw materials and the preparation method are the same as those in Example 2.

[0081] The difference between Example 4 and Example 2 is that different modifiers are selected in the preparation process of the modified anti-wear filler; the modifier in Example 2 is a mixed modifier composed of N-(3-hydrogenated rosin acid acyl-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride in a weight ratio of 3:2.

[0082] The modified anti-wear filler is prepared by the following method:

[0083] (1) Add an appropriate amount of melamine to methanol, stir and dissolve to obtain a melamine methanol solution with a mass fraction of 8%;

[0084] (2) Weighing silicon nitride and zirconium oxide in a weight ratio of 5:1, then adding melamine methanol solution and mixing evenly, and then evaporating the methanol to obtain a mixture;

[0085] (3) calcining the mixture at 500°C for 3 h in an argon atmosphere to obtain a calcined product;

[0086] (4) mixing the calcined product with a solution containing 5% by mass of a modifier to obtain a modified mixture;

[0087] (5) drying the modified mixture to obtain the modified anti-wear filler;

[0088] In step (2), the ratio of the total weight of silicon nitride and zirconium oxide to the melamine methanol solution is 1 kg:2 L;

[0089] In step (4), the ratio of the calcined product to the solution containing the modifier is 1 kg:2 L; the modifier is composed of N-(3-hydrogenated abietic acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride in a weight ratio of 3:2.

[0090] Example 5 Preparation of high-strength concrete additive

[0091] Raw materials by weight: 45 parts of fly ash; 15 parts of montmorillonite; 15 parts of modified anti-wear filler; 2 parts of sodium lignin sulfonate as a water reducer; 3 parts of dispersant;

[0092] The preparation method of the modified anti-wear filler is the same as that of Example 4;

[0093] The dispersant is selected from sodium hexametaphosphate.

[0094] Preparation method: fly ash, montmorillonite, modified anti-wear filler, water reducer and dispersant are uniformly mixed to obtain the high-strength concrete additive.

[0095] Example 6 Preparation of high-strength concrete additive

[0096] The composition of raw materials by weight and the preparation method are the same as those in Example 5.

[0097] The difference between Example 6 and Example 5 is that the dispersant is selected differently; the rest is the same as Example 5.

[0098] The dispersant in Example 6 is lauryl acylammonium methylsulfate.

[0099] Example 7 Preparation of high-strength concrete additive

[0100] The composition of raw materials by weight and the preparation method are the same as those in Example 5.

[0101] The difference between Example 7 and Example 5 is that the dispersant is selected differently; the rest is the same as Example 5.

[0102] The dispersant in Example 7 is N-octadecyl octadecanoic acid amide.

[0103] Example 8 Preparation of high-strength concrete additive

[0104] The composition of raw materials by weight and the preparation method are the same as those in Example 5.

[0105] The difference between Example 8 and Example 5 is that the dispersant is selected differently; the rest is the same as Example 5.

[0106] The dispersant in Example 8 is composed of sodium hexametaphosphate, lauryl acylammonium methylsulfate and N-octadecyl octadecanoamide in a weight ratio of 1:1:1.

[0107] Example 9 Preparation of high-strength concrete additive

[0108] The composition of raw materials by weight and the preparation method are the same as those in Example 5.

[0109] The difference between Example 9 and Example 5 is that the dispersant is selected differently; the rest is the same as Example 5.

[0110] The dispersant in Example 9 is composed of sodium hexametaphosphate and lauryl acylammonium methylsulfate in a weight ratio of 1:1.

[0111] Example 10 Preparation of high-strength concrete additive

[0112] The composition of raw materials by weight and the preparation method are the same as those in Example 5.

[0113] The difference between Example 10 and Example 5 is that the dispersant is selected differently; the rest is the same as Example 5.

[0114] The dispersant in Example 10 is composed of lauryl acylammonium methylsulfate and N-octadecyl octadecanoamide in a weight ratio of 1:1.

[0115] Experimental example

[0116] The high-strength concrete additives prepared in Examples 1 to 10 were mixed with 325 cement and fine sand in a ratio of 1:2:2, and then water was added and stirred to form concrete. The 28-day compressive strength and 28-day abrasion loss per unit area of ​​the concrete containing the high-strength concrete additive were tested according to the methods in GB / T 50081-2019. The experimental results are shown in Table 1.

[0117] Table 1. Effect of the high-strength concrete additive of the present invention on concrete properties

[0118]

[0119] As can be seen from the experimental results in Table 1, the concrete obtained by adding the high-strength concrete additive described in Example 1 has a higher 28d compressive strength and a relatively low 28d wear per unit area; this shows that adding a high-strength concrete additive containing anti-wear fillers composed of silicon nitride and zirconium oxide to concrete can make the concrete have higher strength and certain wear resistance.

[0120] As can be seen from the experimental results in Table 1, the concrete obtained by adding the high-strength concrete additives described in Examples 2 and 3 has a significantly reduced 28-day wear per unit area, and its 28-day compressive strength is also significantly improved, compared to the concrete obtained by adding the high-strength concrete additives described in Example 1. This shows that the modified anti-wear filler obtained by modifying the anti-wear filler composed of silicon nitride and zirconium oxide by the method described in the present invention can significantly improve the wear resistance of concrete compared to the unmodified anti-wear filler composed of silicon nitride and zirconium oxide. In addition, it can also effectively improve the compressive strength of concrete.

[0121] The experimental results in Table 1 show that the concrete prepared with the high-strength concrete additive described in Example 4 significantly reduced the 28-day wear per unit area compared to the concrete prepared with the high-strength concrete additive described in Example 1. This reduction was significantly greater than that achieved with the high-strength concrete additives described in Examples 2 and 3. This demonstrates that the choice of modifier significantly influences the wear resistance of the resulting modified anti-wear filler, and that different modifiers enhance the wear resistance of concrete to varying degrees. When the modified anti-wear filler prepared by using a mixed modifier consisting of N-(3-hydrogenated rosin acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride as the modifier is selected, the degree of improvement in the wear resistance of concrete is significantly higher than that of the modified anti-wear filler prepared by using a single N-(3-hydrogenated rosin acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride or tetradecyldimethylbenzylammonium chloride as the modifier; the modified anti-wear filler prepared by using a mixed modifier consisting of N-(3-hydrogenated rosin acid-2-hydroxy)-propyl-N,N,N-triethanolammonium chloride and tetradecyldimethylbenzylammonium chloride can synergistically improve the wear resistance of concrete.

[0122] As can be seen from the experimental results in Table 1, the concrete obtained by adding the high-strength concrete additives described in Examples 5-7 and Examples 9 and 10 did not significantly reduce the 28-day abrasion loss per unit area compared to the concrete obtained by adding the high-strength concrete additive described in Example 4, nor did its 28-day compressive strength significantly increase. However, the concrete obtained by adding the high-strength concrete additive described in Example 8 further significantly reduced the 28-day abrasion loss per unit area compared to the concrete obtained by adding the high-strength concrete additive described in Example 4, and the reduction was significantly greater than that of the concrete obtained by adding the high-strength concrete additives described in Examples 5-7 and Examples 9 and 10. At the same time, its 28-day compressive strength was further significantly increased, and the increase was significantly greater than that of the concrete obtained by adding the high-strength concrete additives described in Examples 5-7 and Examples 9 and 10. This shows that general dispersants or dispersant combinations cannot enable the high-strength concrete additive of the present invention comprising fly ash, montmorillonite and anti-wear filler to further significantly improve the compressive strength and wear resistance of concrete; only by using a mixed dispersant composed of sodium hexametaphosphate, lauryl acylammonium trimethyl sulfate and N-octadecyl octadecanoic acid amide can the high-strength concrete additive of the present invention further significantly improve the compressive strength and wear resistance of concrete; however, using one or a combination of any two of sodium hexametaphosphate, lauryl acylammonium trimethyl sulfate and N-octadecyl octadecanoic acid amide cannot enable the high-strength concrete additive of the present invention to further significantly improve the compressive strength and wear resistance of concrete.

Claims

1. A high-strength concrete additive, characterized in that: Contains the following components in parts by weight: 30-50 parts of fly ash; 10-20 parts of montmorillonite; 10-20 parts of anti-wear filler; 1-5 parts of water reducing agent; The anti-wear filler is a modified anti-wear filler; the modified anti-wear filler is prepared by the following method: (1) adding melamine into methanol and stirring to dissolve to obtain a melamine methanol solution; (2) silicon nitride and zirconium oxide are taken, and then melamine methanol solution is added and mixed evenly, and then the methanol is evaporated to obtain a mixture; (3) calcining the mixture at 400-600°C for 2-4 hours in an inert gas atmosphere to obtain a calcined product; (4) mixing the calcined product with a solution containing a modifier to obtain a modified mixture; (5) drying the modified mixture to obtain the modified anti-wear filler; The modifier is selected from N-(3-hydrogenated rosin acid acyl-2-hydroxy)-propyl-N,N,N-triethanol ammonium chloride or tetradecyl dimethyl benzyl ammonium chloride.

2. The high-strength concrete additive according to claim 1, characterized in that: Contains the following components in parts by weight: 40-50 parts of fly ash; 15-20 parts of montmorillonite; 15-20 parts of anti-wear filler; 1-3 parts of water reducing agent.

3. The high-strength concrete additive according to claim 1, characterized in that: The weight ratio of silicon nitride to zirconium oxide in the anti-wear filler is 4-6:

1.

4. The high-strength concrete additive according to claim 1, characterized in that: The mass fraction of melamine in the melamine methanol solution is 5-10%.

5. The high-strength concrete additive according to claim 1, characterized in that: In step (2), the ratio of the total weight of silicon nitride and zirconium oxide to the amount of melamine methanol solution is 1 kg: 2-3 L.

6. The high-strength concrete additive according to claim 1, characterized in that: In step (3), the ratio of the calcined product to the solution containing the modifier is 1 kg: 2-3 L.

7. The high-strength concrete additive according to claim 1, characterized in that: The mass fraction of the modifier in the solution containing the modifier in step (2) is 4-6%.

8. The method for preparing the high-strength concrete additive according to any one of claims 1 to 7, characterized in that: The following steps are included: The high-strength concrete additive is obtained by uniformly mixing fly ash, montmorillonite, anti-wear filler and water reducing agent.

Citation Information

Cited By

  • Concrete composite additive based on coal gangue and preparation method thereof

    CN120192110A

  • A concrete composite additive based on coal gangue and preparation method thereof

    CN120192110B